Development of a laboratory model three phase static var compensator - Ahmad @ Awang, Rosli (1994)
This project is to develop a laboratory model tliree-phase fixed capacitors, thyristor controlled reactors (FC-TCR) static var compensator (SVC). It is capable of performing dynamic power factor correction and terminal voltage stabilization at the receiving end of a model radial transmission line. It is a'computer based compensator unit driven by software written in Q-basic language. The control circuit detect the zero-crossing of each individual line-to-line voltage waveform and upon receiving voltage signal from digital to analog converter(DAQ, generate the controlled gating pulses for the triggering hardware. The conduction angles of all of the thyristors are the same and varies accordingly with the serial command signal from the computer. Conducting thyristor controlled reactors generate a desirable variable susceptances require for compensating.